EFEKTIFITAS PEMBELAJARAN MATEMATIKA MODEL KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) KELAS VII SMP ISLAM KOTA PEKALONGAN TAHUN 2009/2010 MATERI SEGIEMPAT - Muchamad Subali Noto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
This is an experimental research, and the research question is that will the Teams Games  Tournament  (TGT)  Cooperative  Model  in  learning  quadrilateral  at  SMP Islam Pekalongan be effective?, Field study is chosen to find out the populations of SMP  Islam Pekalongan  that consists of 8 classes, using the  random technique sampling and determined that class VII(8) as the control class and class VII(3) as the  experiment  class.  The  variables;  students’  activeness  is  as  the  independent variable  and  process  skill  is  as  the  dependent  variable.  The  data  is  derived  from the  learning  test  achievement  and  experiment  sheets.  The  research  method  is descriptive, the  analysis  of the t test  sample  and  regression. The  hypothesis  tests using  simultaneous  study  too  find  out  the  students’  achievement  in  classical  or individual,  and  the  influence  of  students’  activeness  and  the  skill  process  to  the learning  achievement.  The  results  of  the  research  are  that  the  learning  is considered  to  be  effective,  signed  by  3  indicators,  they  are;  (1)  the  students’ achievement  is  up  to  the  classical  criteria  that is  69,33  more  than  KKM  65,  and the  individual  achievement is  75%,  (2)  the  students’ activeness and  skill  process have  positive  influences  to  the  students’  achievement,  the  activeness  has  an influence to the learning achievement to 80,30%, the influence of the skill process is 69,00%, and both of them are 81,50%, (3) the experiment class’s achievement is 69,33 better than the control class in average 61,60%.Key words: Learning effectiveness, TGT, Quadrilateral